(untitled) (BIRDEM Medical Journal, 2020)
Background: Cirrhosis of liver is one of the important cause of liver disease in our country. Worldwide as well as in our country the most common cause of liver cirrhosis is due to hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Many of the patients with cirrhosis of liver do not know that they have already been affected with this kind of viral induced liver disease. They do not know how it occurs and what to be done afterwards due to lack of adequate knowledge with awareness and lack of proper guidance by the general physicians. The aim of our study is to see the demographic and virological profiles of cirrhosis of liver with their possible modes of transmission. Methods: This cross-sectional study was carried out during the period of July 2018 to June 2019 in Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM) General Hospital, Dhaka, Bangladesh. Cirrhosis of liver was diagnosed mostly with the help of ultrasonography of whole abdomen and endoscopy of upper GIT. In few selected cases fibroscan of liver and liver biopsy were done. Results: This study included 724 patients who had cirrhosis of liver. Of them 276 cases had viral and 448 cases had non viral causes. We studied among 276 cases who had viral etiology. Male predominated over female (M: F=2.1:1) at presentation. Male patients were mostly in service (25.7%) and female patients were housewives (27.5%).Most of the patients were diabetic (53.3%), within 41-50 years of age (29.0%), urban background (67.0%) and mostly present as compensated than decompensated stage of cirrhosis of liver and it had significant association (p value .007) with liver cirrhosis. Among viral etiology HBV(70.7%)is the leading cause of cirrhosis of liver followed by HCV(28.6%).Both HBV and HCV infections were found more in male than female and it is significantly associated with cirrhosis of liver (p value .001).HBV infections were found more in non-diabetic patients and it is highly significant(p value .000) but HCV infections were found more in diabetic patients but it is not significant(p value .194).Regarding transmission of virus, male patients gave past history of haircut and shaving in barber shop in 37.76% cases for HBV, 27.66% cases for HCV positive patient and for female gave past history of childbirth by midwifery (‘dhais’) in 36.36% cases for HBV, 12.5% cases for HCV positive patient. In case of HBV transmission, history of surgery (23.14%),blood transfusion(4.71%),family history (24.7%) of HBV and in case of HCV history of surgery(16.47%), blood transfusion(9.01%),family history(1.57%) of HCV were found in both male and female patient. History of high risk exposure to multiple sexual partner were found more in HBV than HCV positive male patient. Conclusion: Cirrhosis of liver is more common in male than female patient between the age of 41-50, mostly urban background and present to us more at compensated stage. HBV infection is more common in male non diabetic and HCV infection is more common in female diabetic patient. Male patients with past history of haircut or shaving in barber shop and for female patient with history of delivery by midwifery (‘dhais’) more for HBV than HCV compared to history of blood transfusion more for HCV than HBV positive patient had an important role for virus transmission in our country. Birdem Med J 2020; 10(3): 192-199